Intravenous Thrombolysis is Effective in Mild Stroke Patients with an Admission NIHSS Score of 3 to 5 - Zhang, Kai; Han, Lin (Current neurovascular research, 2023)
The role of intravenous thrombolysis in patients with acute mild ischemic stroke remains highly controversial. Therefore, this study aims to analyze the efficacy and safety of intravenous thrombolysis in patients with mild ischemic stroke based on admission National Institutes of Health Stroke Scale (NIHSS) score. The present study enrolled 507 patients with acute mild ischemic stroke admitted within 4.5 hours of symptom onset with an admission NIHSS score of 0 to 5. Patients were assigned to two groups based on admission NIHSS scores of 0 to 2 and 3 to 5, and subsequent analyses compared functional outcomes between thrombotic and non-thrombotic patients within these groups. The primary outcome was a modified Rankin score (mRS) of 0 or 1 at 90 days, representing functional independence. The safety outcomes were symptomatic intracranial hemorrhage (sICH), early neurological deterioration (END), and the rate of stroke recurrence within 90 days. Among the 267 patients with NIHSS scores of 0 to 2, 112 (41.9%) patients received intravenous thrombolysis. Overall, thrombolysis administration did not significantly improve the patient's functional prognoses at 90 days (adjusted OR=1.046, 95%CI=0.587-1.863, p = 0.878). However, there was a marked increase in the risk of sICH (p = 0.030). Of the 240 patients with NIHSS scores of 3 to 5, 155 (64.6%) patients received intravenous thrombolysis, resulting in a significant improvement in 90-day functional prognosis (adjusted OR=3.284, 95%CI=1.876- 5.749, p < 0.001) compared to those that did not receive thrombolysis intervention. Importantly, there was no significant increase in sICH incidence (adjusted OR=2.770, 95%CI=0.313-24.51, p = 0.360). There were no statistically significant differences in END or the rate of stroke recurrence within 90 days between thrombotic and non-thrombotic groups. Intravenous thrombolysis is safe and effective in patients with baseline NIHSS scores of 3 to 5. In contrast, it did not improve 90-day functional outcomes in patients with NIHSS scores of 0 to 2 and instead increased the risk of sICH.